The Representation of Roma in the Romanian Media During COVID-19: Performing Control Through Discursive-Performative Repertoires - Chiruta, Ionut (Frontiers in Political Science, 2021)
This article investigates the narratives employed by the Romanian media in covering the development of COVID-19 in Roma communities in Romania. This paper aims to contribute to academic literature on Romani studies, particularly in Central and Eastern Europe, by adopting as its case study the town of Ţăndărei, a small town in the south of Romania, which in early 2020 was widely reported by Romanian media during both the pre- and post-quarantine period. The contributions rest on anchoring the study in post-foundational theory and media studies to understand the performativity of Roma identity and the discursive-performative practices of control employed by the Romania media in the first half of 2020. Aroused by the influx of ethnic Romani returning from Western Europe, the Romanian mainstream media expanded its coverage through sensationalist narratives and depictions of lawlessness and criminality. These branded the ethnic minority as a scapegoat for the spreading of the virus. Relying on critical social theory, this study attempts to understand how Roma have been portrayed during the Coronavirus crisis. Simultaneously, this paper resonates with current Roma theories about media discourses maintaining and reinforcing a sense of marginality for Roma communities. To understand the dynamics of Romanian media discourses, this study employs NVivo software tools and language-in-use discourse analysis to examine the headlines and sub headlines of approximately 300 articles that have covered COVID-19 developments in Roma communities between February and July 2020. The findings from the study indicate that the media first focused on exploiting the sensationalism of the episodes involving Roma. Second, the media employed a logic of polarization to assist the authorities in retaking control of the pandemic and health crisis from Romania. The impact of the current study underlines the need to pay close attention to the dynamics of crises when activating historical patterns of stigma vis-à-vis Roma communities in Eastern Europe.